Peran Profesi Guru Dalam Membangun Nilai-Nilai Karakter Siswa - Bintang Ridzky Dwi Putra; Isnaini Sapitri Br Purba; Muhammad Wafi Siregar; Nurul Atika Hasibuan; Rasyita Dewi Lubis; Zahra Nabila Iqbal; Rizki Daulay (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This research presents the role of teachers in building student character values in one of the educational institutions in Medan. Structured interviews were conducted to be able to obtain data and information with certainty from the interviewees, then the results of the interviews were transcribed and checked. This study provides three important themes including the value of student character values, the role of teachers in building student character and challenges and strategies in changing student character. This study confirms that teachers have an important role in every student character development, by communicating in coaching students and building student character through existing organizations.